Control ciudadano del gasto público y social de la Contraloría General de la República, 2021 - Urbina Kcomt, Sheyla Mitsue (2022)
Objective: analyze how citizen control of public spending is related to the social control of the Comptroller General of the Republic in Ancash, 2021. Method: the approach was essentially quantitative, the type of study was established as applied scientific, descriptive-correlational (explanatory) and, all of this under a non-experimental-cross-sectional design. The study population was made up of subjects who are the object of social control. Thus, the sample was made up of 26 public workers from the Social Control Unit of Ancash and 100 people from the population of Ancash. The sample was defined according to non-probabilistic convenience sampling and the following criteria: type of sampling, population associated with the observed problem, and integration and exception criteria. The key data collection technique used was the survey, while the instruments used were closed-ended questionnaires with a multilevel Likert scale. Results: the inferential correlational analysis under Spearman's t-test model revealed that, the p-value (Bilateral Sig) was "0.000", therefore, the researcher's hypothesis was not rejected. Also, Spearman's ρ (rho) coefficient showed a value of 0.834; this means that there is a direct and high two-way association. Conclusion: the statistical evidence was sufficiently consistent to conclude that there is a representative association between citizen control of public expenditure and social control of the Office of the Comptroller General of the Republic, 2021; for this particular case.